Study on Influence of Number of Permanent Magnetic Pole Pair on Transmission Characteristic of Radial Modulated Permanent Magnetic Gear - Lei Xiao; Hai Zhang; Baoyu Xu; Chengzhe Wang; Xiaoru Hao (Jixie chuandong)
For permanent magnetic gears （PMGs）， each transmission ratio can be made by several combinations of the numbers of magnetic pole pairs （NMPP） on the driving and driven rotors. In order to investigate the influence of NMPP on transmission efficiency and output torque， transmission ratio i=5 is selected， PMGs with 6 combinations of NMPP and corresponding two groups （each group has 6 combinations） are analyzed， the 6 combinations of NMPP on driving/driven rotors are 2/10， 3/15， …， 7/35. Finite element analysis （FEA）simulations indicate that variations of output torque to NMPP on driving rotor （Ph） are quadratic curves with peak values occurring at Ph=4， variations of transmission efficiency to Ph also show quadratic curves basically but with slow change and a little higher values occurring at Ph=4~7. So it is concluded that considering output torque and transmission efficiency together， for PMGs with transmission ratio i being close to 5， the NMPP on driving/driven rotors （Ph /Pl） should be selected as 4/19 to get a better transmission characteristics.